2020
DOI: 10.1002/cam4.3434
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value and potential molecular mechanism of the downregulation of MAOA in hepatocellular carcinoma tissues

Abstract: Background Hepatocellular carcinoma (HCC) remains one of the most common cancers worldwide and tends to be detected at an advanced stage. More effective biomarkers for HCC screening and prognosis assessment are needed and the mechanisms of HCC require further exploration. The role of MAOA in HCC has not been intensively investigated. Methods In‐house tissue microarrays, genechips, and RNAsequencing datasets were integrated to explore the expression status and the clinical value of MAOA in HCC. Immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Our team previously found that NC was a tumor inhibitor in HCC [31][32][33][34][35][36], and in this study, miR-125b-2-3p could be considered a protective factor in HCC. Thus, an in vivo experiment was designed to explore the relationship between NC and miR-125b-2-3p.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our team previously found that NC was a tumor inhibitor in HCC [31][32][33][34][35][36], and in this study, miR-125b-2-3p could be considered a protective factor in HCC. Thus, an in vivo experiment was designed to explore the relationship between NC and miR-125b-2-3p.…”
Section: Discussionmentioning
confidence: 55%
“…The anti-tumor effects of traditional Chinese medicine in HCC were researched by our team, and we found that nitidine chloride (NC) was an inhibitor of HCC onset and development [31][32][33][34][35][36]. In our study, miR-125b-2-3p was associated with the progression and prognosis of HCC; however, it was still unknown whether NC could act on miR-125b-2-3p.…”
Section: The Correlation Between Nitidine Chloride and Mir-125b-2-3p In Hepatocellular Carcinoma Cellsmentioning
confidence: 71%
“…As a highly malignant tumor with a poor prognosis, hepatocellular carcinoma (HCC) seriously threatens human health and causes a great economic burden to patients and society ( Chen et al, 2016 ; Yan and Fan, 2019 ). Although plenty of studies in recent years have reported a variety of biomarkers for HCC, the currently available are still insufficient ( Pang et al, 2020 ; Xing et al, 2020 ; Cai et al, 2021 ; Dolicka et al, 2021 ). Therefore, it is necessary to identify novel biomarkers for early diagnosis and prognostic monitoring of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the potential signal pathways of differentially expressed FOXM1 in regulating ESCC development, a clusterPro ler package supported by R v3.6.2 was used to predict signal pathways in gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Then, we listed the genes enriched in the top three KEGG terms and entered them into the search tool to retrieve interacting genes (STRING) to structure the protein-protein interaction (PPI) network as previously reported (34), (35), (36), (37). Next, we downloaded the PPI network analysis result and screened the top nine signi cant hub genes through degree conversion; the CytoHubba module achieved this step in cytoscape v3.7.1.…”
Section: Exploration Of Foxm1 Potential Mechanisms In Regulating Esccmentioning
confidence: 99%